Effect Of Mid-Cycle Pgf2α And Gnrh At Ai On Conception Rate, Plasma Progesterone And Biochemical Profile In Repeat Breeding Crossbred Cows - Patel, K.R.; Dhami, A.J.; Hadiya, K.K.; Savalia, K.K.; Killedar, Ankita; Patel , S.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
This study was carried out in AMUL milk shed area on 30 crossbred cows, comprising 20 repeat breeding and 10 normal cyclic ones to evaluate their clinical response to mid-cycle PGF2α and AI + GnRH protocol (10 RB cows each) and to monitor plasma progesterone, protein and cholesterol profile at different time intervals post-treatment/AI. Nine out of 10 cows responded within 82.67±4.22 hrs to mid-cycle PGF2α (25 mg, i/m) treatment. The first service and overall conception rates of 3 cycles were 40 and 80 % in mid-cycle PGF2α group; 30 and 70 % in AI + GnRH (20 µg, i/m) group; and 50 and 80 % in normal cyclic control group. The plasma progesterone levels in mid cycle PGF2α protocol on day of treatment, AI and day 21 post-AI were 6.25±1.41, 0.60±0.10 and 9.53±1.66 ng/ml (P<0.01) in conceived and 1.93±0.11, 0.67±0.27 and 0.88±0.13 ng/ml in non conceived animals. The P4 levels in AI + GnRH protocol on day 0 (AI) and 21 post-AI were 0.47±0.23, and 9.75±2.63 ng/ml (P<0.01) in conceived and 0.43±0.08 and 0.69±0.11 ng/ml in non-conceived cows. The variation in P4 between conceived and non-conceived animals was also significant (P<0.01) on the day of treatment in mid cycle PG group. The P4 levels in normal cyclic control cows on day 0 and 21 post-AI were 0.24±0.04 and 10.48±1.34 ng/ml (P<0.01) in conceived cows and 0.41±0.15 and 0.63±0.11 ng/ml in non-conceived cows, respectively. In mid-cycle PGF2α protocol, the plasma total cholesterol concentrations in conceived and non-conceived animals were 155.20±14.40 vs 230.25±7.74 mg/dl (P<0.05) and and total protein 12.39±0.25 vs 12.16±0.28 g/ dl, with significant variation between sampling days in cholesterol only. In AI + GnRH protocol and in normal cyclic control groups, no significant variation was found in total cholesterol and total protein levels between sampling days and between pregnancy status. In general, both the treatment protocols improved conception rates and plasma P4 profile in repeat breeding cows, though there was no significant influence on plasma protein and cholesterol profile.